Policy Debate | Ecuador’s Yasuní-ITT Initiative : What Can We Learn from its Failure? - Pamela L. Martin; Imme Scholz (Revue Internationale de Politique de Développement)
Editor’s note: This paper is a contribution to the ‘Policy Debate’ section of International Development Policy. In this section, academics, policy-makers and practioners engage in a dialogue on global development challenges. Papers are copy-edited but not peer-reviewed. Instead, the initial thematic contribution is followed by critical comments and reactions from scholars and/or policy-makers.In her article ‘Pay to Preserve: The Global Politics of Ecuador’s Yasuní-ITT Proposal’, published in DevPol’s special issue on  Energy and Development in 2011, Pamela L. Martin, Associate Professor of Politics at the Coastal Carolina University in Conway, South Carolina, provided a favourable outlook on Ecuador’s innovative environmental governance mechanism. Accordingly, its unique potential lay in its objective of contributing towards sustainable development and social justice and in case of success, the author even predicted a possible replication in other developing countries. Despite its benefits, the initiative was abandoned in 2013. In this paper, Martin revisits the initiative and analyses the reasons for its failure, namely President Correa’s public pursuit of a Plan B, entering into negotiations with oil firms interested to explore the ITT reserves. Moreover, the initiative was in stark competition with the national REDD+ programme, the mainstream policy approach to reduce emissions from deforestation and forest degradation against payments, which is being negotiated under the United Nations Framework Convention on Climate Change (UNFCCC).Pamela L. Martin’s article is followed by a response by Dr. Imme Scholz, Deputy Director of the German Development Institute/Deutsches Institut für Entwicklungspolitik (DIE). She examines why Germany, as the largest European donor, withdrew its support for the Yasuní-ITT Initiative.Readers who are intetested are invited to contribute to this policy debate on our blog .Download the whole debate (.pdf file)